Computational Predictions for OCD Pathophysiology and Treatment: A Review - Szalisznyó, Krisztina; Silverstein, David N. (Frontiers in Psychiatry, 2021)
Obsessive compulsive disorder (OCD) can manifest as a debilitating disease with high degrees of co-morbidity as well as clinical and etiological heterogenity. However, the underlying pathophysiology is not clearly understood. Computational psychiatry is an emerging field in which behavior and its neural correlates are quantitatively analyzed and computational models are developed to improve understanding of disorders and comparing model evidence to observations. The aim is to more precisely understand psychiatric illnesses. Such computational and theoretical approaches may also enable more personalized treatments. Yet, these methodological approaches are not self-evident for clinicians with a traditional medical background. In this mini-review, we summarize a selection of computational OCD models, computational analysis frameworks and also review the model predictions from a perspective of possible personalized treatment. The reviewed computational approaches used dynamical systems frameworks, machine learning methods for analyzing and classifying patient data and Bayesian interpretations of probability for model selection were also included. The computational dissection of the underlying pathology is expected to narrow the explanatory gap between the phenomenological nosology and the neuropathophysiological background of this heterogeneous disorder. It may also contribute to develop biologically grounded and more informed dimensional taxonomies of psychopathology.